How the digital economy enhances the grain supply chain resilience in China: exploring the moderating effects of government innovation-driven - Chang, Jinrui; Jiang, Huiming; Liu, Jianbo; Li, Mingyang (Frontiers in Sustainable Food Systems, 2024)
Introduction Ensuring food security in the new development paradigm urgently requires increasing the grain supply chain resilience. In order to clarify how can significantly enhance grain supply chain resilience, to demonstrate the relationship between the digital economy, government innovation-driven and grain supply chain resilience is necessary. To specify how the government can effectively perform its macro-regulatory functions, the government innovation-driven is reflected by government innovation-driven planning and government innovation-driven investment, respectively. Methods The data of 31 provinces in China from 2011 to 2021 have been used. The panel fixed effects model, moderating effects model and threshold effects model have been selected to analyze. Results Digital economy has a stronger enhancement effect on grain supply chain resilience; Government innovation-driven has an increased moderating effect on digital economy enhance grain supply chain resilience; The enhancement effect of digital economy and the moderating effect of government innovation-driven are differentiated between China’s functional zones of grain production; And the threshold effect of government innovation-driven planning shows a process of digestion and absorption, which accumulating to 0.018 will emerge a multiplier effect. Government innovation-driven investment is higher than 0.026, which can have a promoted moderating effect. Discussion To expand the depth of integration of the digital economy, accurately government innovation-driven, the focus should be on attracting innovative talent, who can construct the perpetual motion machine mode of “external promote + internal drive,” so as to strengthen the robustness of the grain supply chain.